Pengaruh Media terhadap BudayaTradisionil, Lokal, Kontemporer dan Budaya Popular - Amal, Riski (Pascasarjana IAIN Lhokseumawe, 2019)
Culture is derived from the word buddhayah (Sanskrit), meaning the mind or intellect. In Latin, the word culture comes from Colere, which berartti tilling the soil. So culture in general can be interpreted as